Fiscal Policy for Growth - Ley, Eduardo (World Bank, Washington, DC, 2012)
While the term 'fiscal space' is new, the issue is quite old. Fiscal space refers to availability of budgetary resources for a specific purpose, typically growth-enhancing investment uses, without jeopardizing the sustainability of the government's financial position, or the stability of the economy. The recent interest in fiscal space originated as a reaction to International Monetary Fund (IMF), supported fiscal-adjustment programs that by focusing too narrowly on fiscal-deficit targets often ignored the quality of the underlying adjustment. Affected countries meanwhile advocated for fiscal space for investments in physical and human infrastructure crucial for economic growth. The IMF independent evaluation office, in their study on fiscal Adjustment in IMF supported programs acknowledged this problem, observing that 'much of the fiscal adjustment achieved is through measures that do not assure long-term sustainability and flexibility of fiscal systems to future shocks'. In effect, the improvement of the fiscal balance in the context of IMF-supported programs too often relied heavily in cuts in public investment that improve today's government cash flow at the expense of future economic growth.